In The Collection And Study Skills Kwlh After Use Of Self-Table Strategy Article Teaching Methods At Colleges Of Education Students - Farman, Shaza A. (Humanities Journal of University of Zakho, 2018)
Following the strategy of self-table in the collection and study skill Oakedzab Article teaching methods at colleges of education students. Research Vredita: No statistically significant differences animate at a significance level (0.05) between the average scores of students in the experimental group who are studying methods of teaching material self-table strategy and the average score students in the control group in the collection of material teaching methods There are no statistically significant differences animate at a significance level (0.05) between the average difference in test scores (dimensional) for students of the two sets of experimental and control research in academic skills. Chose researchers determined empirically a set partially, a design control group randomized Alachtaaratkon research community current students of colleges of education at the University of Baghdad (Ibn Rushd, Ibn al-Haytham, girls), has reached the research community (2800) students from the third grade, the study morning reached current members of the research sample (72) students Researchers keen on equality of the two sets of research in a number of variables that may affect the Results of the experiment and prepared researchers MAP test and formulated paragraphs achievement test which consists of 80 paragraph 60% of the behavioral objectives 60 paragraph multiple-choice and 20 questions pans and conducted researchers statistical analysis difficult, convenience and strength discriminatory and effective alternatives wrong and obtained the honesty and Althbatopnt researchers scale study skills specific five skills b and corrupted scale of 66 paragraph reality 14 paragraphs of skill recall and 14 paragraph of skill blogging and 11 Vqrhlmharh time management and 17 paragraphs of the skill to read and review the sources and 10 paragraphs to skill management Alachtbarazart results than a clear statistically significant for the students of the experimental group who studied material teaching methods using strategy table self students control group who studied teaching methods and material according to the steps the usual way (lecture, discussion) in the collection and study skills (except for time management skill) Itaúj experiment